Assessment of defecation disorders using high-resolution MRI-defecography - Ioana Duca; Ramona Boja; Dan Lucian Dumitrascu (Biomedical Papers, 2023)
Aims. The aim of this retrospective study was to try to find correlations between different diagnoses established by clinical examination, anorectal manometry and MRI-defecography and, the association with psychiatric disorders. Methods. 44 patients (median age 53.81 years) presenting with intestinal motility disorders and who underwent clinical, biological and psychiatric examination, dynamic defecographic-MRI (resting, squeezing, straining, defecation and evacuation phases), anorectal manometry, colonoscopy. MRI was performed using the 1,5 T. Results. MRI-defecography revealed the following changes: anismus (16), rectocele (12), pelvic floor dysfunction (6), peritoneocele (2), cervical-cystic-ptosis (1), rectal prolapse (6), and in 1 case the examination was normal. Hypertonic anal sphincter (16) and lack of defecation reflex (12) at anorectal manometry correlated with anismus in all patients at MRI-defecography. Lack of inhibitor anal reflex (6) was associated with rectocele (4), cervix-cysto-ptosis (1) and peritoneocele (2). Anxiety (11), depression (6) and anxiety-depressive disorders (10) were found in 27/44, somatization disorders in 9/44 and no psychiatric changes in 8/44 cases. Conclusion. As multiparous women are at risk for outlet obstruction constipation, MRI-defecography is suggested in this category. There is good correlation between diagnosis using anorectal manometry and MRI-defecography in patients with terminal constipation and anismus. Lower defecation dysfunction is often associated with psychiatric disorders.